Flow injection analysis of paracetamol using a biomimetic sensor as a sensitive and selective amperometric detector - Oliveira, Mariana C. Q. [UNESP]; Lanza, Marcos R. V.; Tanaka, Auro A.; Sotomayor, Maria Del Pilar Taboada [UNESP] (Royal Soc Chemistry, 2010)
This work describes the coupling of a biomimetic sensor to a flow injection system for the sensitive determination of paracetamol. The sensor was prepared as previously described in the literature (M. D. P. T. Sotomayor, A. Sigoli, M. R. V. Lanza, A. A. Tanaka and L. T. Kubota, J. Braz. Chem. Soc., 2008, 19, 734) by modifying a glassy carbon electrode surface with a Nafion (R) membrane doped with iron tetrapyridinoporphyrazine (FeTPyPz), a biomimetic catalyst of the P450 enzyme. The performance of the sensor for paracetamol detection was investigated and optimized in a flow injection system (FIA) using a wall jet electrochemical cell. Under optimized conditions a wide linear response range (1.0 x 10(-5) to 5.0 x 10(-2) mol L(-1)) was obtained, with a sensitivity of 2579 (+/- 129) mu A L mu mol(-1). The detection and quantification limits of the sensor for paracetamol in the FIA system were 1.0 and 3.5 mu mol L(-1), respectively. The analytical frequency was 51 samples h(-1), and over a period of five days (320 determinations) the biosensor maintained practically the same response. The system was successfully applied to paracetamol quantification in seven pharmaceutical formulations and in water samples from six rivers in São Paulo State, Brazil.